p53 restoration in small cell lung cancer identifies a latent cyclophilin-dependent necrosis mechanism - Jonuelle Acosta; Qinglan Li; Nelson F. Freeburg; Nivitha Murali; Alexandra Indeglia; Grant P. Grothusen; Michelle Cicchini; Hung Mai; Amy C. Gladstein; Keren M. Adler; Katherine R. Doerig; Jinyang Li; et al. (Nature Communications, 2023)
Abstract The p53 tumor suppressor regulates multiple context-dependent tumor suppressive programs. Although p53 is mutated in ~90% of small cell lung cancer (SCLC) tumors, how p53 mediates tumor suppression in this context is unknown. Here, using a mouse model of SCLC in which endogenous p53 expression can be conditionally and temporally regulated, we show that SCLC tumors maintain a requirement for p53 inactivation. However, we identify tumor subtype heterogeneity between SCLC tumors such that p53 reactivation induces senescence in a subset of tumors, while in others, p53 induces necrosis. We pinpoint cyclophilins as critical determinants of a p53-induced transcriptional program that is specific to SCLC tumors and cell lines poised to undergo p53-mediated necrosis. Importantly, inhibition of cyclophilin isomerase activity, or genetic ablation of specific cyclophilin genes, suppresses p53-mediated necrosis by limiting p53 transcriptional output without impacting p53 chromatin binding. Our study demonstrates that intertumoral heterogeneity in SCLC influences the biological response to p53 restoration, describes a cyclophilin-dependent mechanism of p53-regulated cell death, and uncovers putative mechanisms for the treatment of this most-recalcitrant tumor type.